(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The effect of extract of Acacia Nolitica pod on the corrosion inhibition of LM 6 aluminium alloy in 1M NaOH was studied using weight loss, gasometric, and open circuit potential techniques. Corrosion rates were found to reduce in the presence of the inhibitor. The inhibition efficiency was found to increase with increase in the concentration of the inhibitor and decreased with increase in the temperature. Thermodynamic parameters showed that the adsorption of the inhibitor on the metal surface is a spontaneous process and that the adsorption was via a physisorption mechanism. The adsorption process fitted perfectly with the Langmuir adsorption isotherm indicating that the extract was strongly adsorbed on the aluminium alloy surface. Morphology of the surface was examined by scanning electron microscopy (SEM) in the absence and presence of 0.5%v/v of the used inhibitor which confirmed the existence of a protective film of inhibitor molecule on the metal surface.